Effect of Organoclay Content and Molecular Weight on Cellulose Acetate Nanocomposites Properties - Guarda-Moraga, A; Rodriguez-Mercado, F; Bruna-Bugueno, J; Galotto-Lopez, M (2012)
Nanocomposites based on cellulose acetate (CA), a commercial organoclay (Cloisite30B) and triethyl citrate (TEC) were obtained using a solution casting method. Different nanocomposites were prepared according to different organoclay contents (2.5, 5.0, 7.5 and 10.0 wt.%) and molecular weight of cellulose acetate (Mn 30,000 and 50,000). The properties of the nanocomposites were evaluated by means of opacity index, X-ray diffraction (XRD), differential scanning calorimetry (DSC), mechanical (modulus of elasticity, tensile strength and elongation at break), scanning electron microscopy (SEM) and oxygen transmission rate (OTR) measurements. All obtained nanocomposites showed the intercalation of polymer inside the clay structure which was slightly favored for nanocomposites with CA 30,000. Important changes on the opacity index, mechanical properties, glass transition and melting temperatures, crystalline fraction, oxygen permeability and fracture morphology of nanocomposite films were observed according to the increase of organoclay content. On the other hand, intercalation level and oxygen permeability showed some differences with the molecular weight of cellulose acetate. © 2012 Elsevier Ltd. All rights reserved.